WDR5-H3K4me3 epigenetic axis regulates OPN expression to compensate PD-L1 function to promote pancreatic cancer immune escape - Jennifer L Waller; Chunwan Lu; Kebin Liu; John D Klement; Dafeng Yang; Zhuoqi Liu; Alyssa D Merting; Dakota Poschel; Thomas Albers; Huidong Shi (Journal for ImmunoTherapy of Cancer)
Background Despite PD-L1 (Programmed death receptor ligand-1) expression on tumor cells and cytotoxic T lymphocytes tumor infiltration in the tumor microenvironment, human pancreatic cancer stands out as one of the human cancers that does not respond to immune checkpoint inhibitor (ICI) immunotherapy. Epigenome dysregulation has emerged as a major mechanism in T cell exhaustion and non-response to ICI immunotherapy, we, therefore, aimed at testing the hypothesis that an epigenetic mechanism compensates PD-L1 function to render pancreatic cancer non-response to ICI immunotherapy.Methods Two orthotopic pancreatic tumor mouse models were used for chromatin immunoprecipitation-Seq and RNA-Seq to identify genome-wide dysregulation of H3K4me3 and gene expression. Human pancreatic tumor and serum were analyzed for osteopontin (OPN) protein level and for correlation with patient prognosis. OPN and PD-L1 cellular location were determined in the tumors using flow cytometry. The function of WDR5-H3K4me3 axis in OPN expression were determined by Western blotting. The function of H3K4me3-OPN axis in pancreatic cancer immune escape and response to ICI immunotherapy was determined in an orthotopic pancreatic tumor mouse model.Results Mouse pancreatic tumors have a genome-wide increase in H3K4me3 deposition as compared with normal pancreas. OPN and its receptor CD44 were identified being upregulated in pancreatic tumors by their promoter H3K4me3 deposition. OPN protein is increased in both tumor cells and tumor-infiltrating immune cells in human pancreatic carcinoma and is inversely correlated with pancreatic cancer patient survival. OPN is primarily expressed in tumor cells and monocytic myeloid-derived suppressor cells (M-MDSCs), whereas PD-L1 is expressed in tumor cells, M-MDSCs, polymorphonuclear MDSCs and tumor-associated macrophages. WDR5 is essential for H3K4me3-specific histone methyltransferase activity that regulates OPN expression in tumor cells and MDSCs. Inhibition of WDR5 significantly decreased OPN protein level. Inhibition of WDR5 or knocking out of OPN suppressed orthotopic mouse pancreatic tumor growth. Inhibition of WDR5 also significantly increased efficacy of anti-PD-1 immunotherapy in suppression of mouse pancreatic tumor growth in vivo.Conclusions OPN compensates PD-L1 function to promote pancreatic cancer immune escape. Pharmacological inhibition of the WDR5-H3K4me3 epigenetic axis is effective in suppressing pancreatic tumor immune escape and in improving efficacy of anti-PD-1 immunotherapy in pancreatic cancer.